2019
DOI: 10.1101/805556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene-environment interactions characterized by single embryo transcriptomics

Abstract: Fetal Alcohol Spectrum Disorders (FASD) describes the full range of defects that result from prenatal alcohol exposure. The clinical diagnosis of Fetal Alcohol Syndrome (FAS) is the most severe outcome, characterized by facial dysmorphism and neurological deficits. Gene-ethanol interactions underlie susceptibility to FASD but we lack a clear understanding of the genetic risk factors. Here, we leverage the genetic tractability of zebrafish to address this problem. We first show that vangl2, a member of the Wnt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Ethanol exposure during development can induce holoprosencephaly (HPE) [ 42 , 43 ]. HPE is characterized by defective rostroventral midline patterning of the forebrain with an array of other abnormalities, including failure of the forebrain to form hemispheres and cyclopia [ 44 , 45 ].…”
Section: Consequences Of Ethanol Exposure During Early Zebrafish Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol exposure during development can induce holoprosencephaly (HPE) [ 42 , 43 ]. HPE is characterized by defective rostroventral midline patterning of the forebrain with an array of other abnormalities, including failure of the forebrain to form hemispheres and cyclopia [ 44 , 45 ].…”
Section: Consequences Of Ethanol Exposure During Early Zebrafish Deve...mentioning
confidence: 99%
“…Studies have also shown that phenotypes produced by embryonic ethanol exposure such as cyclopia and other midfacial defects can arise from cell death of neural crest cells. Furthermore, shh developmental signaling was indirectly displaced by a synergistic interaction between ethanol and cyclopamine, a shh pathway inhibitor [ 43 ]. A rescue experiment using shh mRNA injection into ethanol treated zebrafish embryos reduced ethanol induced phenotypes, indicating that shh signaling is disrupted in FAS [ 47 ].…”
Section: Consequences Of Ethanol Exposure During Early Zebrafish Deve...mentioning
confidence: 99%